2009
DOI: 10.1097/cji.0b013e31818fe167
|View full text |Cite
|
Sign up to set email alerts
|

Combining an EGF-based Cancer Vaccine With Chemotherapy in Advanced Nonsmall Cell Lung Cancer

Abstract: An epidermal growth factor (EGF) vaccine was given before and after standard first line chemotherapy to patients with advanced nonsmall cell lung cancer (NSCLC), to investigate the immunologic and clinical results in a phase 1 study. Twenty patients diagnosed with advanced NSCLC were recruited. Two vaccinations were given before the first line of chemotherapy treatment, with subsequent monthly vaccination after concluding chemotherapy. The EGF vaccination dose was increased compared with previous trials; the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 29 publications
1
46
0
4
Order By: Relevance
“…MS was performed in the 5 most immunogenic of a total of 74 2D fractions to identify protein (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI37646DS1). This MS analysis revealed that immunogenic fractions contained the following well-known TAAs: EGFR (19,20) and Her-2/neu (21,22). To determine whether either of these TAAs was recognized by a population of preexisting memory T cells, we next used well-described synthetic long peptides (EGFR 479-528 , Her-2/neu 351-384 ) (23) as test antigens in ELISPOT assays using blood from the same patient.…”
Section: T Cell Response To a Defined Antigen After Pf2d Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…MS was performed in the 5 most immunogenic of a total of 74 2D fractions to identify protein (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI37646DS1). This MS analysis revealed that immunogenic fractions contained the following well-known TAAs: EGFR (19,20) and Her-2/neu (21,22). To determine whether either of these TAAs was recognized by a population of preexisting memory T cells, we next used well-described synthetic long peptides (EGFR 479-528 , Her-2/neu 351-384 ) (23) as test antigens in ELISPOT assays using blood from the same patient.…”
Section: T Cell Response To a Defined Antigen After Pf2d Fractionationmentioning
confidence: 99%
“…immunogenic epitope in more detail, we synthesized overlapping 20-meric peptides of the respective region ( Figure 6C) and identified S100A9 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] as the immunogenic epitope ( Figure 6D). This epitope was recognized both by CD8 + and CD4 + T cells of patient NCH550 ( Figure 6E).…”
Section: Figurementioning
confidence: 99%
“…This vaccine elicits antibodies against self-EGF and a decrease in plasma EGF concentration [21][22][23][24][25][26][27][28][29]. It has been tested in several clinical trials for the treatment of advanced Non-Small Cell Lung Cancer (NSCLC), in which a significant correlation has been found among anti-EGF antibody titers, decrease in EGF concentration and patient´s survival.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the HAGE antigen is immunogenic and is highly associated with TILs, one should consider targeting HAGE along with other CSAs using immunotherapeutic interventions in conjunction with chemotherapy for TNBC. Although in the past, cancer vaccines have had a poor clinical track record due to poor clinical results (34), in recent trials using immunotherapy, clinical outcomes have shown improved progression-free survival, or overall survival (35)(36)(37)(38). In fact, it is proposed that chemotherapies could be used to condition the immune system and tumor, and create an environment in which cancer vaccines have a better chance of success (34,39).…”
Section: Discussionmentioning
confidence: 99%